2016
DOI: 10.1021/acsomega.6b00354
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Scanning of Arg10–Teixobactin: Deciphering the Role of Hydrophobic and Hydrophilic Residues

Abstract: Teixobactin is a recently discovered antimicrobial cyclodepsipeptide with good activity against Gram positive bacteria. Taking Arg10–teixobactin as a reference, where the nonproteinogenic residue l-allo-enduracididine was substituted by arginine, a lysine scan was performed to identify the importance of keeping the balance between hydrophilic and hydrophobic amino acids for the antimicrobial activities of this peptide family. Thus, the substitution of four isoleucine residues present in the natural sequence by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…This indicates that a minimum of four carbon atoms is necessary for optimal hydrophobic interactions. The importance of a non‐polar group at position 11 was also evident in previous studies, which showed that the substitution of Ile with a polar residue, such as Lys, abolished the antibacterial activity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that a minimum of four carbon atoms is necessary for optimal hydrophobic interactions. The importance of a non‐polar group at position 11 was also evident in previous studies, which showed that the substitution of Ile with a polar residue, such as Lys, abolished the antibacterial activity …”
Section: Resultsmentioning
confidence: 99%
“…Teixobactin ( 1 ), comprised of a 13‐membered depsipeptide core and a tethered linear heptapeptide, offers multiple sites for synthetic modifications to improve its potency and efficacy. In less than three years since its discovery, more than a hundred analogues have been synthesised by various research groups in the hope of elucidating its structure–activity relationships (SARs) . The biological activities of these analogues and the different synthetic strategies reported have been comprehensively reviewed .…”
Section: Introductionmentioning
confidence: 99%
“…This means hydrophobic interactions are expected to play significant roles in Txb's activity. Granted, most known Txb analogs with substituted mid-chain hydrophobic residues lose their antimicrobial activities,11,15,16,22 indicating that hydrophobic interactions are indeed essential for Txb–lipid II binding.…”
Section: Discussionmentioning
confidence: 99%
“…The Gram‐negative lipid II binding of the other two analogues investigated (with Ser to Lys substitution at position 3 or d ‐Gln to d ‐Lys at position 4 of the linear tail of teixobactin) was approximately 100‐fold weaker, with dissociation constants of 63 and 38 μ m for analogues 4 and 5 , respectively. These analogues were designed with the results from the Albericio group in mind, which showed that positions 3 and 4 Lys substitutions are tolerated and activity is largely maintained …”
Section: Figurementioning
confidence: 99%